The Antioxidant Guaiacol Exerts Fungicidal Activity Against Fungal Growth and Deoxynivalenol Production in Fusarium graminearum - Gao, Tao; Zhang, Yao; Shi, Jianrong; Mohamed, Sherif Ramzy; Xu, Jianhong; Liu, Xin (Frontiers in Microbiology, 2021)
The main component of creosote obtained from dry wood distillation - guaiacol - is a natural antioxidant that has been widely used in pharmaceutical and food preservation applications. However, the antifungal mechanism of guaiacol against phytopathogens remains unclear. In this study, we found that guaiacol exerts inhibitory effects against mycelial growth, conidial formation and germination, and deoxynivalenol (DON) biosynthesis in Fusarium graminearum in a dose-dependent manner. The median effective concentration （EC50） value of guaiacol for the standard F. graminearum strain PH-1 was 1.838 mM. Guaiacol strongly inhibited conidial production and germination. The antifungal effects of guaiacol may be attributed to its capability to cause damage to the cell membrane by disrupting Ca2+ transport channels. In addition, the decreased malondialdehyde (MDA) levels and catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) activity by guaiacol treatment indicate that guaiacol displays activity against DON production by modulating the oxidative response in F. graminearum. Taken together, this study revealed the potentials of antioxidant in inhibiting mycotoxins in F. graminearum.